Trends in cardiovascular disease risk factors by obesity level in adults in the United States, NHANES 1999‐2010 - Saydah, Sharon; Bullard, Kai McKeever; Cheng, Yiling; Ali, Mohammed K.; Gregg, Edward W.; Geiss, Linda; Imperatore, Giuseppina (Obesity (Silver Spring, Md.), 2014)
Objective To assess whether trends in cardiovascular disease (CVD) risk factors by among overweight and obese US adults have improved. Methods The study included 10,568 adults 18 years and older who participated in National Health and Nutrition Examination Survey 1999‐2010. CVD risk factors included diabetes (self‐reported diagnosis, glycated hemoglobin ≥6.5%, or fasting plasma glucose ≥126mg/dl), hypertension (treatment or blood pressure ≥140/90 mmHg), dyslipidemia (treatment or non‐HDL cholesterol ≥160 mg/dl), and smoking (self‐report or cotinine levels ≥10 ng/ml). The prevalence and temporal trends of CVD risk factors for each BMI group were estimated. Results In 2007‐2010, the prevalence of diabetes, hypertension, and dyslipidemia was highest among obese (18.5%, 35.7%, 49.7%, respectively) followed by overweight (8.2%, 26.4%, 44.2%, respectively) and normal weight adults (5.4%, 19.8%, 28.6%, respectively). Smoking exposure was highest among normal weight (29.8%) followed by overweight (24.8%) and obese adults (24.6%). From 1999‐2002 to 2007‐2010, untreated hypertension decreased among obese and overweight adults and untreated dyslipidemia decreased for all weight groups. There were no significant temporal changes in smoking across BMI groups. Conclusions Despite decreases in untreated risk factors, it is important to improve the CVD risk profile of overweight and obese US adults.